THE INFLUENCE OF FIRM SIZE, PROFITABILITY, SOLVABILITY, REPUTATION OF THE AUDITORS AND AUDIT COMMITTEE ON THE TIMELINESS REPORTING OF MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE IN 2015 – 2017 - Pane, Dedy Hernanda (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to analyse the effect of firm size, profitability, solvability, auditor?s reputation and audit committee on the timeliness of financial reporting of manufacturing companies on the Indonesian Stock Exchange. This type of research is quantitative research using secondary data collection techniques in the form of financial statements of companies listed on the Indonesia Stock Exchange. The population of this study is manufacturing companies listed on the Indonesia stock exchange. With the criteria that the company has submitted financial statements in 2015 until 2017. Data is processed using multiple regression analysis. The results of the multiple regression analysis used show that company size, profitability and solvency have a significant effect, but the reputation of the auditor and audit committee is not significant to the timeliness of financial reporting.